A Metamorphic Origin for Europa's Ocean. Issue 18 (15th September 2021) - Melwani Daswani, Mohit; Vance, Steven D.; Mayne, Matthew J.; Glein, Christopher R.
Abstract: Europa likely contains an iron‐rich metal core. For it to have formed, temperatures within Europa reached ≳ 1250 K. Going up to that temperature, accreted chondritic minerals — for example, carbonates and phyllosilicates — would partially devolatilize. Here, we compute the amounts and compositions of exsolved volatiles. We find that volatiles released from the interior would have carried solutes, redox‐sensitive species, and could have generated a carbonic ocean in excess of Europa's present‐day hydrosphere, and potentially an early CO 2 atmosphere. No late delivery of cometary water was necessary. Contrasting with prior work, CO 2 could be the most abundant solute in the ocean, followed by Ca 2 +, SO 4 2 −, and HCO 3 − . However, gypsum precipitation going from the seafloor to the ice shell decreases the dissolved S/Cl ratio, such that Cl > S at the shallowest depths, consistent with recently inferred endogenous chlorides at Europa's surface. Gypsum would form a 3–10 km thick sedimentary layer at the seafloor. Plain Language Summary: It is likely that Jupiter's moon Europa hosts a deep ocean underneath its surface ice shell. Telescopes and spacecraft have observed chlorine‐bearing salts on the surface, but we do not yet know what they mean for the chemical composition of the ocean, or how the ocean came to be. Here, we test whether the breakdown of minerals containing volatile elements (hydrogen, carbon, sulfur, and chlorine) inside Europa might have released enough water to produce the ocean. The breakdown of these minerals generally happens at high temperature, but how hot did Europa's interior get? NASA's Galileo spacecraft confirmed that Europa probably has an iron‐rich core, and such cores can only form at high temperature: at least 1250 K. Knowing this, we model the effect that heat had on the minerals (a process known as metamorphism) and calculate how much water would be released, as volatile‐rich minerals transform into volatile‐free minerals. We find that this process could release massive amounts of carbon dioxide, more than enough water to form Europa's present ocean, and produce sulfate and carbonate minerals. Chlorine released would be more abundant in the ocean's shallower depths, perhaps explaining the telescope observations. Key Points: Devolatilization of early Europa's rocky interior may have generated a mildly acidic ocean Heating drove outgassing of up to 1–270 bar CO2, perhaps as an early atmosphere since lost, or captured as a large clathrate reservoir Calcium, sulfate, and carbonate salts precipitate at the seafloor, while chloride is abundant nearer the ice shell